Per Oral Endoscopic Myotomy (POEM) - Reavis, Kevin M. (Springer International Publishing : Imprint: Springer, 2017)
This text is designed to present a comprehensive and state-of the-art approach to the current and future status of POEM. Sections address preliminary issues faced by surgeons and gastroenterologists who are interested in implementing this procedure into their treatment armamentarium. These areas include the evolution of the technique, training and credentialing, as well as tools and platforms commonly used for POEM. Subsequent chapters focus on specific disease processes, and future applications of the technique. Written by experts in POEM, Per Oral Endoscopic Myotomy (POEM) addresses patient selection, pre-operative considerations, technique, and avoiding complications. A brief editorial review of the existing literature addressing the particular topic follows in each section. The text concludes with chapters on emerging and future applications. Extensive endoscopic images and illustrations make this an interactive text for General Surgeons, Surgical Endoscopists, Gastroenterologists, and associated sub-specialists.
Keywords: Medicine.; General practice (Medicine).; Gastroenterology.; Surgery.; Minimally invasive surgery.; elektronické knihy; electronic books